HUBUNGAN KOMUNIKASI TERAPEUTIK PERAWAT DENGAN KECEMASAN ANAK USIA PRASEKOLAH AKIBAT HOSPITALISASI - Qurrotul Aeni; Andriyani Mustika Nurwijayanti; Muhammad Khabib Burhanuddin Iqomh (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2019)
Introduction: anxiety is a condition that will be experienced by children who experience hospitalization and must get attention and management. Anxiety during hospitalization that is not properly addressed will hinder treatment and affect child development. The purpose of the study: to determine the relationship between therapeutic communication nurses and the anxiety of preschool children due to hospitalizationMethod: The study design used descriptive correlation with a cross-sectional approach. The number of samples is 31 with purposive sampling. Collecting research data using a questionnaire.Results: The results showed a majority of therapeutic communication was 61.3%, anxiety in children due to hospitalization of 100% with severe anxiety was 58.1%, there was a relationship between therapeutic communication and children's anxiety (p = 0.001). Suggestions need to be carried out further research on the factors that influence the low therapeutic communication in nurses.Discussion: The results of the statistical analysis using the Spearman's Rho test got p value 0.001 (p <0.05) the relationship between therapeutic communication and the anxiety of pre-school age children who experienced hospitalization, therapeutic communication can be used as an action to prevent anxiety due to hospitalization in pre-school age children.Suggestion: need to do further research on the factors that influence the low therapeutic communication in nurses Keywords: therapeutic communication, anxiety, hospitalization.